G20 coal subsidies: Tracking government support to a fading industry - Ipek Gencsu; Shelagh Whitley; Leo Roberts; Christopher Beaton; Han Chen; Alex Doukas; Anna Geddes; Ivetta Gerasimchuk; Lourdes Sanchez; Anissa Suharsono (Overseas Development Institute (ODI), 2019)
G20 countries have a critical role to play in leading efforts to combat climate change, as they account for 79% of global greenhouse gas emissions. In 2009, they committed to phasing out fossil fuel subsidies in the medium term, and since then many have played an important part in driving forward climate action internationally. However, a decade on from this commitment, G20 governments continue to provide billions of dollars of support for the production and consumption of fossil fuels, spending at least 63.9 billion per year on coal alone, the most polluting fossil fuel. They have also neglected to define or document the full extent of their subsidies. This research tracks each G20 country's progress in phasing out subsidies to the production and consumption of coal (including coal-fired power), looking at fiscal support, public finance, and state-owned enterprise investment. The report summarises key findings from 18 parallel country briefs, with accompanying data sheets that list all the support identified for each country.
Keywords: 330